HLA-A, B antigens and alpha 1-antitrypsin phenotypes in nodal generalised osteoarthritis and erosive osteoarthritis. - Pattrick, M (1989)
HLA-A, B and alpha 1-antitrypsin phenotypes were studied in 90 unrelated patients with established nodal generalised osteoarthritis (OA). Compared with standard reference populations, independently increased frequency of the HLA-A1B8 and MZ alpha 1-antitrypsin phenotypes were observed (27% v 11.5%, relative risk 2.79, and 12% v 3.6%, relative risk 3.73 respectively). These associations related to developed of nodal generalised OA rather than to severity as judged by the summated radiographic scores for hand OA. Ten patients had marked subchondral radiographic erosions and were further classified as erosive OA; these patients had an increased frequency of the MS alpha 1-antitrypsin phenotype (30% v 9%) and higher radiographic OA scores corrected for presence of erosions. This first report of two independent genetic markers in nodal generalised OA is of interest in relation to the increasingly recognised inflammatory component of the osteoarthritis process.